América Latina y el tercer mundo - Herrera, Felipe (Estudios Internacionales, 1977)
Traditional economic relations have had a geographic orientation that could be defined from North to South; that is, between developed and developing nations. In recent years, what we can call South / South cooperation has emerged, that which occurs between Third World countries, characterized by their horizontality. The new conditions of contemporary economic-political reality are favorable to this objective, particularly due to the greater negotiating capacity of an important part of the Third World in terms of the control of fuels and essential raw materials for the growth of the international economy. However, this new reality does not yet have systems or regimes that facilitate this cooperation. In this paper some of the forms that this common labor can take are systematized.